2023
DOI: 10.47626/2237-6089-2021-0337
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use in self-isolation during the COVID-19 pandemic: a cross-sectional survey in Brazil

Abstract: Objectives: To assess alcohol use and perceived change in alcohol consumption (before and during the pandemic) in Brazilians during the COVID-19 pandemic, its correlates, and association with depressive, anxiety and co-occurring depressive and anxiety symptoms (D&A).Methods: This is a cross-sectional study comprising 992 individuals in self-isolation.A self-reported questionnaire was used to assess whether participants were drinking during self-isolation and whether they changed their drinking behavior (drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…Furthermore, alcohol sales and consumption by all metrics decreased in the US during periods with a high incidence of COVID-19 (Moskatel & Slusky, 2023). Studies in Brazil (Moura et al, 2023), Germany (Deeken et al, 2022), Australia (Bade et al, 2021), and others (Acuf et al, 2022), similarly found that alcohol consumption was in general significantly lower during lockdown periods. However, increased alcohol consumption was significantly associated with both particularly high and particularly low degrees of subjective loneliness (Bragard et al, 2022;Haucke et al, 2024).…”
Section: Figure 3)mentioning
confidence: 87%
“…Furthermore, alcohol sales and consumption by all metrics decreased in the US during periods with a high incidence of COVID-19 (Moskatel & Slusky, 2023). Studies in Brazil (Moura et al, 2023), Germany (Deeken et al, 2022), Australia (Bade et al, 2021), and others (Acuf et al, 2022), similarly found that alcohol consumption was in general significantly lower during lockdown periods. However, increased alcohol consumption was significantly associated with both particularly high and particularly low degrees of subjective loneliness (Bragard et al, 2022;Haucke et al, 2024).…”
Section: Figure 3)mentioning
confidence: 87%
“…Avaliando as mudanças predispostas pela pandemia quanto ao uso de álcool, Moura et al (2021), em um estudo transversal brasileiro, analisaram o consumo alcoólico durante o período de isolamento por COVID-19 (MOURA et al, 2021). Através de um questionário autoreportado, o consumo de álcool de 992 participantes foi investigado (MOURA et al, 2021). Dos 68,5% que relataram consumo alcoólico, 22,7% denotaram aumento no consumo e 32,5% redução (MOURA et al, 2021).…”
Section: Artigos Originaisunclassified
“…Através de um questionário autoreportado, o consumo de álcool de 992 participantes foi investigado (MOURA et al, 2021). Dos 68,5% que relataram consumo alcoólico, 22,7% denotaram aumento no consumo e 32,5% redução (MOURA et al, 2021). Todavia, houve associação entre ansiedade e depressão e maior ingestão de álcool (MOURA et al, 2021).…”
Section: Artigos Originaisunclassified
See 1 more Smart Citation